METHODICAL SYSTEMS STUDIES OF MATHEMATICS WITH THE USE OF IKT IN THE PROCESS OF PREPARATION OF FUTURE TEACHERS IN INDUSTRY OF GEOMETRY - Grigorieva В.Б. (Journal of Information Technologies in Education (ITE), 2015)
In the article basic aspects are examined informatizations of modern education, which are related to development and introduction in the process of teaching of disciplines in the institute of higher of the methodical systems teaching the primary purpose of which consists in rationalization of intellectual activity due to the use of information technologies of w I l l o w s increase of efficiency and quality of preparation of specialists. In particular, attention the computer-oriented methodical systems is spared teaching which foresee introduction and application of of informative-communication technologies during teaching of mathematical disciplines, to basic principles of construction of such systems and by a necessity to their komponentam which determine educational aims and maintenance of teaching. place and role of subsystem of teaching disciplines of geometrical cycle is in-process certain also, which comes forward an important constituent in the structure of general professional preparation of specialists and in forming of competent personality which answers the modern requirements of development of informative society. The methodological questions of introduction of the noted systems of studies are in-process considered at teaching of mathematical courses of geometrical cycle for the students of pedagogical specialities and value of these systems in geometrical preparation of future teachers of mathematics.